Important Role of Herbal Extracts in the Management of Breast Cancer - Shiv Kumar; Avneet Gupta; Vinod Kumar Gauttam; Karan Sharma; Amar Deepak; Rohit Thakur (International Journal of Ayurveda and Pharma Research, 2023)
Cancer recognized as a serious disorder among population worldwide. Breast cancer has been found common in women. Breast cancer diagnosed patients increasing with passage of time, which bringing the attention of researcher to give more potential strategies to irradiate this ailment from the society. Natural remedies from medicinal plants are well acknowledged from primitive time of decade. Modern and advanced analytical tools successfully overcome the burden of this disease by incorporating raw formulations into suitable dosage forms and their efficacy can be determined through experimental and clinical studies. There are numerous medicinal plants present having pharmacological potential to decreases the breast cancer cell viability by involving various mechanisms and significantly overcome the global burden of this disorder. Our presented study motivated from the burden of breast cancer among people and its treatment from natural sources. However, it is much needed to understand etiology of the disease and its associated causes. We also demonstrated the treatment strategies originated from natural sources that conquer the spectrum of this disorder. There are numerous types of natural products that has preventive and curative role in the management of breast cancer. So, accurate method and terminology required to elevating the demand of health care system from natural sources can overcome breast cancer.